2021
DOI: 10.1186/s12911-021-01398-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing healthcare providers’ attitude and willingness to use information technology in diabetes management

Abstract: Background The use of information technologies could help to improve communications between patients and care providers, might improve overall patient management practice. However, the potential for implementing these patient management options in Ethiopia has not been well documented. This institution-based survey aimed to describe the attitude and willingness of care providers towards the use of information technologies for managing diabetes patients, and factors influencing their interest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The detailed demographic characteristics of participants were described previously. 36 As described in detail previously, 36 the majority of participants were men (61.31%) and 57.6% of them were below the age of 30 years.…”
Section: Resultsmentioning
confidence: 72%
“…The detailed demographic characteristics of participants were described previously. 36 As described in detail previously, 36 the majority of participants were men (61.31%) and 57.6% of them were below the age of 30 years.…”
Section: Resultsmentioning
confidence: 72%
“…It indicated that the lack of access to computers and smartphones can act as a barrier to the implementation of ICTs. 25 Regarding behaviors related to telepharmacy, 58.7% of pharmacists met the requirements of practice about using telepharmacy. Telepharmacy could deliver outstanding benefits.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with the Ethiopian study, wherein 83% of healthcare providers were willing to use one or more ICTs to support long-term patients. 25 A study in the United States on Telehealth showed that 28.57% of participants were likely to use ICTs in healthcare. 26 This variance might be due to differences in study population and the time of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the intention and skill of using computers should be a major point of attention for teaching hospitals who wish to improve their care providers' attitudes to remote monitoring and willingness in using information technologies. Besides, the awareness of professionals is crucial for improving willingness [12]. Undoubtedly, researchers investigated and published a theoretical model to elucidate user's information technology acceptance and use, for example, the theory of reasoned action [13,14], the theory of planned behaviour [15,16], besides the technology acceptance model (TAM) [17,18], and customer adoption of information technology in the direction of a unified view model [18].…”
Section: Introductionmentioning
confidence: 99%